Volume 2: Aircraft Engine; Coal, Biomass and Alternative Fuels; Cycle Innovations 2013
DOI: 10.1115/gt2013-95079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Defects and Damage in Aircraft Engines on the Exhaust Jet

Abstract: The inspection of aero engines is a complex and time-consuming process, often requiring the disassembling of the engine or boroscopic examinations. The development of a method to locate and characterize defects and damage at an early stage, without disassembling the engine would accelerate the inspection process. For that purpose, the spatial density distribution pattern of the exhaust jet of aircraft engines may be measured with the Background Oriented Schlieren method (BOS). The hypothesis is that defects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…In that case, damages at the real engine can be detected with appropriate exhaust jet diagnostics without disassembling the engine. The feasibility of this approach has already been shown in first steps [1][2][3][4].…”
Section: Introduction and Methodical Approachmentioning
confidence: 99%
“…In that case, damages at the real engine can be detected with appropriate exhaust jet diagnostics without disassembling the engine. The feasibility of this approach has already been shown in first steps [1][2][3][4].…”
Section: Introduction and Methodical Approachmentioning
confidence: 99%
“…The worst-case defect was a complete shutdown of one burner but it was also shown that even small temperature differences have an impact on exhaust jet patterns of density and temperature. In further work, Adamczuk et al 2 investigated the influence of different hot gas path defects on the density patterns at the outlet plane of a jet engine. The simulated defects included the complete shut-down of a burner, the loss of trailing edge material in the second rotor and stator of a two-stage high-pressure-turbine (HPT), and the increase of the clearance gap between the blade tip and the casing of the second stage rotor of the HPT.…”
Section: Introductionmentioning
confidence: 98%
“…The method is based on the hypothesis that defects in the combustion chamber lead to characteristic flow temperature patterns in the exhaust jet. These patterns can be measured and allow the classification of damage without having to disassemble the engine, which helps to reduce time and cost during maintenance, repair and overhaul (MRO) (Adamczuk et al, 2013;Hauptmann et al, 2015). To assess damage, the mixing of these patterns in the turbine section must be understood.…”
Section: Introductionmentioning
confidence: 99%